2022
DOI: 10.21608/eajbsg.2022.238167
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal and Antibiotic Resistance in Bacteria from a Wastewater Treatment Plant

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…This observation corroborated the study of Hacioglu and Tosunoglu [ 38 ] in which high resistance of heavy metal-resistant bacteria isolated from an aquatic species at Kavak Delta to similar antibiotics was observed. Similarly, Omotayo et al [ 39 ] reported that the heavy metal-resistant bacteria isolated from wastewater treatment plant exhibited resistance to two or more classes of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This observation corroborated the study of Hacioglu and Tosunoglu [ 38 ] in which high resistance of heavy metal-resistant bacteria isolated from an aquatic species at Kavak Delta to similar antibiotics was observed. Similarly, Omotayo et al [ 39 ] reported that the heavy metal-resistant bacteria isolated from wastewater treatment plant exhibited resistance to two or more classes of antibiotics.…”
Section: Discussionmentioning
confidence: 99%